北極域研究・観測拠点:スバールバル・ニーオルスン基地の現状と今後 - 宮岡, 宏; 塩原, 匡貴; 内田, 雅己; 後藤, 大輔; 榎本, 浩之; Hiroshi, Miyaoka; Masataka, Shiobara; Masami, Uchida; Daisuke, Goto; Hiroyuki, Enomoto (2017)
第8回極域科学シンポジウム/横断セッション：[IA] 北極国際連携拠点の新展開 12月8日（金）国立極地研究所 2階大会議室 The Eighth Symposium on Polar Science/Interdisciplinary sessions: [IA] New insights of overseas research stations in the Arctic Fri. 8 Dec./2F Auditorium, National Institute of Polar Research conference object